Peer Reviewers of JMH Volume 1 Number 4 August 2016 - Editorial Team (Journal of Medicine and Health, 2016)
We would like to thank our peer reviewers for the precious contributions in providing clinical, scientific, and methodological expertise for JMH Volume 1 Number 4. We appreciate every thoughtful review of submitted manuscripts and for making important contributions to improve the scientific quality of articles published in JMH. We listed the names in alphabetical order. Dr.Achadiyani,dr.,M.KesProf. Andreanus A. Soemardji, DEAdr.Andri Rezano,M.Kes,PhDdr. Cindra Paskaria,MKMdr.Cherry Azaria, M.KesDr. dr Diana Krisanti Jasaputra, M.KesDr. Irda Fidriannydr.Jonathan,Sp.Raddr. Limdawati,Sp.PDdr. Lusiana Darsono, M.Kes.Dr. dr. Oeij Anindita Adhika, M.Kes., PA(K)Prof.Dr. Ridad Agoes,MPHdr.Sunny Wangko,M.Si,PA(K)dr. Sylvia Soeng, M.Kes., PA(K)Dr. Wahyu Widowati, M.Si.Prof. dr. Wahyuni Lukita Atmadja, PhD